Prevention and management of lymphocele formation following kidney transplantation - Golriz, Mohammad; Klauß, Miriam; Zeier, Martin; Mehrabi, Arianeb (Transplantation reviews, 2017)
Despite preventive methods, lymphoceles frequently form following kidney transplantation (KTx), with an incidence of 0.6%-51%. Here, we summarize the current strategies for preventing and managing this complication, and describe the approach used in our department. Rapid diagnosis and early treatment of lymphoceles through a well-defined approach can prevent or reduce the risk of organ loss. Diagnosis can be made by ultrasound, computed tomography, or magnetic resonance imaging and laparoscopic fenestration is the current therapy of choice when non-surgical methods fail. Preventive methods should be performed pre-, intra-, and post-operatively. A peritoneal fenestration at the end of KTx seems to be a reasonable method for preventing lymphocele formation.